Inside dinosaurs - Abramson, Andra Serlin; Brougham, Jason; Mehling, Carl. (New York : Sterling, 2010)
Provides an introduction to paleontologists and the work they do, looks at where dinosaurs lived throughout the world, and features fold-out illustrations and information about different kinds of dinosaurs, when they lived, their classification, and their extinction.
"American Museum of Natural History."
Includes fold-out pages.
Includes bibliographical references (p. 48) and index.
Kirkus Review
Kirkus Review, September 2010
7.4
Keywords: Paleontologists -- Juvenile literature; Paleontology -- Juvenile literature; Paleontologists; Paleontology; Paleontologists; Paleontology